OPTIMASI PRODUKSI ANTIBIOTIKA ISOLAT TERPILIH FUNGI ENDOFIT IKD FF-UMI 02 DARI KULIT BUAH DELIMA (Punica granatum L.) DENGAN VARIASI SUMBER KARBON - Rusli Rusli; Nurul Vicky Syfriani; Sumarni Hatta; Muh. Wais (As-Syifaa Jurnal Farmasi, 2017)
Research of endophytic fungi of pomegranate fruit peel (Punica granatum L.), as Anti-free radicals and antibiotic has been done with DIKTI-PKM funding at 2014. It is considered necessary to further research about optimization of antibiotic production from pomegranate fruit peel with variation of carbon source, first step is selection of isolates that have largest inhibition zone and has the most inhibit microbial test, that is endophytic fungi IKD FF-UMI 02 that has activity on Salmonella thypii, Staphylococcus epidermidis, Staphylococcus aureus and Shigella dysenteriae. Determination of growth curve from isolate by inoculating into Potato Dextrose Broth and incubated for 7x24 hours. Every 12 hours the mycelium is weighed to determine its stationary phase. Determination of optimum conditions of fermentation with carbon source such as glucose, galactose, and fructose. Endophytic fungi IKD FF-UMI 02 inoculated and fermented into production medium which is every 12 hours fermentate was taken. The activity was tested using agar diffusion method in Nutrient Agar (NA) against Salmonella thypii, Staphylococcus epidermidis, Staphylococcus aureus and Shigella dysenteriae. Resulted that growth curve of selected endophytic fungi IKD FF-UMI 02 from pomegranate fruit peel show that stationer phase starting on 192 hour and galactose carbon source is show optimum time of antibiotic production on 120 hours with inhibition zone 10,24 mm against Shigella dysenteriae.